Does asthma affect school performance in adolescents? Results from the Swedish population‐based birth cohort BAMSE. Issue 2 (6th February 2018) - Nilsson, Sara; Ödling, Maria; Andersson, Niklas; Bergström, Anna; Kull, Inger
Abstract: Background: Asthma is common among schoolchildren and may influence quality of life and school attendance. However, it is unclear if asthma affects school performance. The aim of this study was to examine whether different phenotypes of asthma affect school performance during adolescence. Methods: The study population consisted of 1715 adolescents from a population‐based birth cohort, followed up to age 16 with questionnaires and clinical examinations. Asthma was defined as at least 4 wheeze episodes or at least 1 wheeze episode in combination with inhaled steroids in the last 12 months. School grades were obtained from Statistics Sweden, and logistic regression analysis was performed to investigate the association between the final overall grade from secondary school and asthma phenotypes. Results: Among the adolescents, 20.8% have had ever asthma; 24.2% early transient, 47.2% school‐age onset, and 24.2% persistent asthma. At 16 years, 7.8% had asthma; 71.7% multimorbidity and 73.9% allergic asthma. A statistically significant association for performing less well was seen for ever asthma (ORadj  = 1.43, 95% CI = 1.09‐1.88). In analyses of asthma onset, an association was seen for school‐age onset (ORadj  = 1.49, CI = 1.02‐2.16) and a tendency for persistent asthma (ORadj  =  1.61, CI = 0.98‐2.66), although with overlapping confidence intervals. Further, adolescents with uncontrolled asthma tended to perform less well (ORadj  = 2.60, CI = 0.87‐7.80) compared to adolescents with partly controlled (ORadj  = 1.12, CI = 0.68‐1.83) and fully controlled (ORadj  = 1.29, CI = 0.55‐3.01) asthma. Conclusions: Our results indicate that asthma impairs school performance in adolescence. Moreover, some evidence suggests the adolescents with asthma during school age and with poorer asthma control to be more likely to perform less well.